DEVELOPMENT OF LEARNING MEDIA MATERIALS OF BUILDING FLAT SIDE SPACES IN SMP/MTs CULTURE BASED ON RELIGION PIDIE COMMUNITY - Raudhya Nafoura; Lukman Ibrahim; Kamarullah Kamarullah; Novi Trina Sari (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2021)
There are religious and cultural problems of the Pidie Community that have not been explored so that they are not properly utilized as a medium for learning mathematics. Researchers try to provide solutions through the development of religious-based cultural mathematics learning media in the form of PowerPoint software and teaching materials. With the aim of identifying various religious and cultural sites in the district that have not been explored as media for learning mathematics, describing the process of developing learning media for various mathematics teaching materials, and testing the validity of learning media development products with flat-sided building materials based on cultural sites in Pidie and Pidie Jaya. With this design, the research begins with activities that are explored and examined the potential use of religious and cultural sites as learning media for various mathematics teaching materials at the junior high school level using the ethnographic method (qualitative approach), research and development (RD) methods. 4D model with a quantitative approach at the product trial stage. The stages taken are the defining stage, the planning stage, the development stage, and the distribution stage. The data techniques in this study were interviews and questionnaires. Validation is carried out by material experts. Based on the results of the validation of the content quality stage of the learning media, it was obtained an average score of 95.36% with the criteria